A preliminary Study on The Use of PET Bottle Waste as The Green Roof Drainage Layer for Thermal Insulator. Issue 1 (November 2021) - Munir, A; Irfandi,; Muslimsyah,; Abdullah,
Abstract: The phenomenon of urban heat island (UHI) and global warming are significant issues now in relation to sustainable urban development. The application of green roofs is an intention to weaken the impact of UHI by reducing heat gain on the building surface that is emitted to the environment. In addition, green roofs also reduce heat transmission from solar radiation received by the roof to the indoor. Utilization of plastic bottle waste from PET ( Polyethylene Terephthalate ) will cut down the weight of the green roof system, which also develops the heat resistance value of the roof. This research is an initial study that suggests a green roof application that is more environmentally friendly with the principle of reusing PET waste as a sustainable building material to increase thermal resistant of the system. The analysis concentrates on describing the thermal behavior of the green roof system with the inclusion of PET bottles as a drainage layer. The investigation was carried out by preparing a cubical model of 60cm x 60 cm x 60 cm with a green roof system. Thermal performances were assessed by measuring the temperature of each layer of the green roof using thermocouple wire. The environmental variables measured were solar intensity, ambient air temperature, and air humidity, where the sensors placed close to the models. This analysis demonstrates the influences of green roofs in reducing solar radiation heat. Even though the decreasing of room temperature between the models was not significantly different, this initial results show that, by introducing PET, still display a further performance in reducing heat gain from solar radiation. However, it is necessary to adjust the evaluation models. Heat accumulation in room raised the indoor temperature to be higher than the roof temperature, so that the behavior of the green roof with the purpose of PET is not obviously distinguishable. A trial model with ventilation opening will release heat from enclosed space and it could evaluate clearly the rate of heat flow from the roof.